1994
DOI: 10.1177/026988119400800407
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of selective serotonin re-uptake inhibitors in depression: a meta-analysis of studies against tricyclic antidepressants

Abstract: A meta-analysis of the efficacy of five selective serotonin re-uptake inhibitors (SSRIs) against non-selective and noradrenergic re-uptake inhibitors (mainly tricyclic antidepressants, TCAs) is presented. Fifty five double- blind studies were identified after excluding those multiply reported or with methodological problems likely to bias the outcome in favour of SSRIs. Standardised effect sizes and 95% confidence intervals were calculated based on the difference in the reduction in mean Hamilton depression ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
1
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(95 citation statements)
references
References 83 publications
7
85
1
2
Order By: Relevance
“…36 However, non suicidal depressive adults did not present changes in serotonin receptor binding in prefrontal cortex. 37 Specific SSRIagents are effective in the treatment of both depressive adults 38 and depressive adolescents. 39 Altered serotonergic function has been noted in depressive children, too.…”
Section: Monoamines In Depressionmentioning
confidence: 99%
“…36 However, non suicidal depressive adults did not present changes in serotonin receptor binding in prefrontal cortex. 37 Specific SSRIagents are effective in the treatment of both depressive adults 38 and depressive adolescents. 39 Altered serotonergic function has been noted in depressive children, too.…”
Section: Monoamines In Depressionmentioning
confidence: 99%
“…Premature attrition results in the loss of outcome data from as many as 30% (Anderson and Tomenson, 1994;Hotopf et al, 1997;Montgomery et al, 1994;Song et al, 1993) of the subjects enrolled in an RCT. There is also a tendency for differential attrition of subjects.…”
Section: Randomized Controlled Trials In the Comparison Of Antidepresmentioning
confidence: 99%
“…Perhaps the most influential example of meta-analyses in mood disorders research is the series by Anderson, Freemantle, and colleagues, which demonstrated that SSRIs are, as a class, comparably effective and significantly better tolerated than TCAs (Anderson, 1998(Anderson, , 2000Anderson and Tomenson, 1994;Song et al, 1993). They also allowed for the detection of differences in subgroup comparisons not apparent in qualitative reviews or single primary studies.…”
Section: Chronology Of Meta-analysis In Antidepressant Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[10][11][12][13] Comparative clinical trials indicate that SSRIs are as effective as TCAs, but relative safety and better acceptability of SSRIs has been the reason to their clinical success over TCAs. [13][14][15][16][17][18] However, published data evaluating and comparing the efficacy of different ADs are lacking in Nepal. This study was designed to compare the efficacy of escitalopram, most selective SSRIs with amitriptyline, a reference standard drug in the treatment of depression.…”
mentioning
confidence: 99%